1956
DOI: 10.1042/bj0630367
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of cerebrospinal fluid and serum proteins in multiple sclerosis with special reference to the Lange colloidal-gold reaction

Abstract: Positive colloidal-gold reactions in the cerebrospinal fluid of patients with multiple sclerosis have been reported as occurring in 29-81 % of fluids examined by various investigators (Freedman & Merritt, 1949). Coagulation of the colloidal gold has been shown to be associated with the y-globulin fraction (Kabat, Moore & Landow, 1942). The concentration of y-globulin in cerebrospinal fluid was determined immunochemically by Yahr, Goldensohn & Kabat (1954), who report an increase in 66-5 % of the multiple-scle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1959
1959
1989
1989

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…[32], an d sim ilar differences have been d e m o n strated previously for o th e r CSF p ro teins [11,14,16,17,20,22,26,28,29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[32], an d sim ilar differences have been d e m o n strated previously for o th e r CSF p ro teins [11,14,16,17,20,22,26,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it would appear th a t all major serum protein fractions may be present in the CSF [17,18,22,26,28], and th a t abnorm al scrum protein concentrations may produce -although to a lesser and inconstant degree -abnorm al CSF protein findings [4,14,17,18,20,22], The CSF protein content, however, is distinct from th a t of serum, as protein fractions, which are found only in the CSF, have been reported [11,12,15,17,19,21,26,28]. Furtherm ore, there is some evidence th a t certain proteins can be produced by the central nervous system and its coverings [14,16,20,22,26,28,29].…”
Section: Ucoprotein C Ontent O F C Erebro-spinal Fluid B Y Allen S mentioning
confidence: 99%
See 1 more Smart Citation
“…The colloidal gold reaction [40,62] utilized 10 tubes containing equal amounts of brilliant cherry-red colloidal gold solution to which cerebrospinal fluid was added. The amount of cerebrospinal fluid to be added to the first tube resulted in its concentration being 1: 10; the concentration of cerebrospinal fluid in each subsequent tube was progressively reduced by one half.…”
Section: Chemistrymentioning
confidence: 99%
“…On the one hand , there were some reports on comparative study of the components of serum and CSF . It is reported that some of the substances [12][13][14][15] found in the CSF were not found in the serum, some others16,17) were found in the serum but only in a small quantity or not at all 14,18) Sialic acid is not present19, 23) in the serum freed of protein by the trichloracetic acid. But there is a report24) that sialic acid is present in the protein-free serum but in a very small amount.…”
Section: Commentmentioning
confidence: 99%